Video quality assessment method: MD-SSIM - Woei-Tan, Loh; Bong, David B.L. (2015)
In this paper, video quality assessment (VQA) for compression losses is the main focus. A new method, MD-SSIM (Mean Squared Error Difference SSIM) is used for detecting the spatial distortion. For the temporal part, the differences of the SSIM scores of each frame are used to form the quality scores. In addition, this method has higher computational speed and competent performance as compared to other existing algorithms.